Effective interventions targeting the mental health of children and young adults: A scoping review. Issue 3 (May 2021) - Bjerre, Natasja; Lillefjell, Monica; Magnus, Eva; Anthun, Kirsti S.
Aims: Children and young adults are in general characterised by good health, but evidence shows increasing mental-health problems. Numerous interventions have been developed to target their mental health, but the effectiveness of these interventions remains varied. In this scoping review, we investigated factors associated with the effectiveness of interventions. Methods: A scoping review based on a three-block search strategy was performed to review the current literature of effective interventions. Each block (interventions, mental health and children and young adults) were operationalised to search terms. Systematic searches were conducted in three electronic databases and supplemented with citation searches, resulting in 51 studies in total. All studies were critically analysed, and a standardised extraction chart was used to systemise the data. Results: Our scoping review revealed a range of factors influencing the effectiveness of interventions. These factors were (a) characteristics of the target group (age, sex and level of baseline symptoms), (b) factors linked to implementation (use of manuals, training of implementers and context) and (c) characteristics of the interventions (universal versus indicated delivery, multiple-domain approaches, level of theory and adjustment to age and socio-economic status). Elements are discussed for each factor. Conclusions: Based on this review, it can be concluded that the use of stepwise, multi-domain approaches incorporating the social networks of the target group, adjusting activities to specific age groups and the social context, training implementers well and using stringent implementation manuals will improve the effectiveness of interventions targeting the mental health of children and young adults.